Diel dissolved organic matter cycling and phytoplankton abundance in four trophic regimes of the South Pacific Ocean - Theresa Barthelmeß; Antonia Cristi; Stacy Deppeler; Karl Safi; Karine Sellegri; Cliff S Law; Anja Engel (PANGAEA, 2025)
Samples were collected in the surface of the Southwestern Pacific Ocean in subtropical, and sub-Antarctic water masses, above the Chatham Rise, and at the entrance of the Cook Strait in well mixed water masses, creating distinct oligotrophic and eutrophic regimes, respectively. Regimes were manifested in phytoplankton, bacterial and viral particle abundances along with Chlorophyll a concentration. Diel cycling of dissolved organic matter (DOM), i.e. of dissolved amino acids (DAA) and combined carbohydrates (DCCHO), was investigated, including their molecular compositions. Subsurface (SUB) waters were sampled via the underway pump system of the ship (6m), while the underlaying water (ULW) was sampled from a working boat. The ULW samples complement the data set.